"Comintern-Type" Complexes in the Balezino Burial Ground of the Polom Culture in the Northern Udmurtia - Elizaveta M. Chernykh (Археология евразийских степей, 2025)
The article presents some aspects of the comparative study of the new Early medieval Balezino burial ground materials in the basin of the Cheptsa. The preliminary dating of the site is within the VI–VII centuries. During excavations, compelling evidence was uncovered for the first time of two distinct burial practices – inhumation and cremation – being utilized in the early Polom period. This feature prompts a renewed examination of the origins of the medieval population in northern Udmurtia. With the emergence of significant new archaeological materials from this period in the Volga-Kama region (among which the Komintern II burial ground holds particular importance), researchers are increasingly focusing on the historical and cultural context of interactions between the populations of the Kama River area and the Middle Volga region. The chronological proximity of the Balezino burial ground to Comintern-type monuments, biritualism, the importance of fire and horse cults in the burial rite, as well as some parallels in the composition of the grave goods (a combination of Kharino and early heraldic sets, moonlike jevelry, sets of beads, including large amber disc-shaped beads) allow us to draw attention to the existence of closer links between two regions.